KADAR ALBUMIN SERUM PENDERITA STROK ISKEMIK DAN STROK HEMORAGIK - Fasni Halil; Hj. Darmawaty ER; Ruland DN Pakasi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
To differentiate the ischemic and hemorrhagic stroke with the most accurate method can be carried out by Computerized Tomography(CT) scan. However, because the restrictor on access and cost, not all patients could gain the advantage of CT scan. Examination ofalbumin is a quick and easy test. The aim of this study was to evaluate the serum albumin level in patient suffering ischemic andhemorrhagic stroke. A cross sectional study of 60 ischemic and hemorrhagic stroke patients was performed at the Neurologic Departmentof Dr. Wahidin Sudirohusodo Hospital Makassar, from March up to August 2008. Albumin – levels was measured using the colorimetricBCG method, using the Cobas Integra 400 Autoanalyser. The data were than analyzed with SPSS 11.5 software and t test. Among the60 samples of the ischemic and hemorrhagic stroke were found mean values of serum albumin level is 3.38 ± 0.120 and hemorrhagicstroke is 3.51 ± 0.0938 with p value is 0.495. There were no significantly different between the serum albumin level of the ischemicand hemorrhagic stroke patients.